2020
DOI: 10.17305/bjbms.2020.5066
|View full text |Cite
|
Sign up to set email alerts
|

Alectinib and lorlatinib function by modulating EMT-related proteins and MMPs in NSCLC metastasis

Abstract: Most advanced non-small cell lung cancer (NSCLC) patients are accompanied by brain metastasis which is the major cause of increased mortality. The fusion rearrangement of anaplastic lymphoma kinase (ALK) gene is an important feature of brain metastasis in lung cancer. The novel ALK inhibitors alectinib and lorlatinib are shown to be effective against NSCLC brain metastasis, while their underlying mechanism of action is unclear. Epithelial–mesenchymal transition (EMT) proteins and matrix metalloproteinases (MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For example, lapatinib, an orally active drug for solid tumours through targeting HER2 and EGFR pathways, has been reported to inhibit the cellular EMT program in multiple cancers 107–109 . Consistently, Clinical drugs targeting ALK, such as alectinib and lorlatinib, have been found to inhibit cellular EMT signalling in lung cancer 110 . Gamma secretase inhibitors of Notch signalling has been confirmed to inhibit EMT in ovarian cancer 111 .…”
Section: Mechanisms Of Cellular Emt Signallingmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, lapatinib, an orally active drug for solid tumours through targeting HER2 and EGFR pathways, has been reported to inhibit the cellular EMT program in multiple cancers 107–109 . Consistently, Clinical drugs targeting ALK, such as alectinib and lorlatinib, have been found to inhibit cellular EMT signalling in lung cancer 110 . Gamma secretase inhibitors of Notch signalling has been confirmed to inhibit EMT in ovarian cancer 111 .…”
Section: Mechanisms Of Cellular Emt Signallingmentioning
confidence: 89%
“… 107 , 108 , 109 Consistently, Clinical drugs targeting ALK, such as alectinib and lorlatinib, have been found to inhibit cellular EMT signalling in lung cancer. 110 Gamma secretase inhibitors of Notch signalling has been confirmed to inhibit EMT in ovarian cancer. 111 Therefore, it has become an increasingly promising anti‐tumour strategy by blocking EMT signalling pathway in cancer cells.…”
Section: Mechanisms Of Cellular Emt Signallingmentioning
confidence: 99%
“…FN1 is also known to play regulatory roles in NSCLC brain metastasis [ 31 ]. When epithelial cells obtain the mesenchymal phenotype, disruption of intercellular tight junctions and blood-brain barrier will facilitate cell migration [ 32 ]. FN1 was detected among LC and NSCLC group by combination of label free and PRM based proteomics and bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Serpin Family A Member 1 was significantly differentially expressed between the BM and LP groups in the current study and another report ( 17 ). It has been reported that epithelial-to-mesenchymal transition–associated proteins and matrix metalloproteinases contribute to BM by modulating the blood-brain barrier ( 18 ). In addition, the high expression of inner membrane mitochondrial protein is closely associated with advanced disease stage and poor patient prognosis in LAC ( 19 ).…”
Section: Discussionmentioning
confidence: 99%